Diazoksit Yanıtsız Hiperinsülinemik Hipoglisemili Bir Olguda Tedavi ve İzlem - Damla Gökşen (Journal of Pediatric Research, 2017)
Hyperinsulinemic hypoglycemia (HH) is the most common reason for persistent and recurrent hypoglycemia in the neonatal and infancy periods. We presented a case diagnosed with HH on the first day of life and who underwent near-total pancreatectomy because of the unresponsiveness to the diazoxide treatment. Despite early diagnosis and management, complications developed due to hypoglycemia and surgery.